Protein phosphatase 1 regulatory subunit 3B gene variation protects against hepatic fat accumulation and fibrosis in individuals at high risk of nonalcoholic fatty liver disease. Issue 6 (25th April 2018) - Dongiovanni, Paola; Meroni, Marica; Mancina, Rosellina M.; Baselli, Guido; Rametta, Raffaela; Pelusi, Serena; Männistö, Ville; Fracanzani, Anna L.; Badiali, Sara; Miele, Luca; Grimaudo, Stefania; Petta, Salvatore; et al.
Abstract : PPP1R3B variation is associated with protection against histological steatosis, dyslipidemia, liver fibrosis and hepatocellular carcinoma in high risk individuals of European descent The mechanisms seems related to down‐modulation of hepatic de novo lipogenesis Abstract : Nonalcoholic fatty liver disease (NAFLD) is a major cause of liver damage and has a strong genetic component. The rs4841132 G>A variant, modulating the expression of protein phosphatase 1 regulatory subunit 3B ( PPP1R3B ), which is involved in glycogen synthesis, has been reported to reduce the risk of NAFLD but at the same time may favor liver disease by facilitating glycogen accumulation. The aim of this study was to assess the impact of rs4841132 on development of histologic steatosis and fibrosis in 1, 388 European individuals in a liver biopsy cohort, on NAFLD hepatocellular carcinoma in a cross‐sectional Italian cohort (n = 132 cases), and on liver disease at the population level in the United Kingdom Biobank cohort. We investigated the underlying mechanism by examining the impact of the variant on gene expression profiles. In the liver biopsy cohort, the rs4841132 minor A allele was associated with protection against steatosis (odds ratio [OR], 0.63; 95% confidence interval [CI], 0.42‐0.95; P = 0.03) and clinically significant fibrosis (OR, 0.35; 95% CI, 0.14‐0.87; P = 0.02) and with reduced circulating cholesterol ( P = 0.02). This translated into protection against hepatocellular carcinoma development (OR, 0.22; 95% CI, 0.07‐0.70; P = 0.01). At the population level, the rs4841132 variation was not associated with nonalcoholic or nonviral diseases of the liver but was associated with lower cholesterol ( P = 1.7 × 10 –8 ). In individuals with obesity, the A allele protecting against steatosis was associated with increased PPP1R3B messenger RNA expression and activation of lipid oxidation and with down‐regulation of pathways related to lipid metabolism, inflammation, and cell cycle. Conclusion : The rs4841132 A allele is associated with protection against hepatic steatosis and fibrosis in individuals at high risk of NAFLD but not in the general population and against dyslipidemia. The mechanism may be related to modulation of PPP1R3B expression and hepatic lipid metabolism. ( Hepatology Communications 2018;2:666‐675)